Navigating change: the role of change management strategies and cultural factors in Saudi Arabian organizations - Rouissi, Chiraz Mohamed (Frontiers in Psychology, 2025)
BackgroundOrganizational change remains a critical challenge in the industrial sectors of the Kingdom of Saudi Arabia, where leadership practices and deep-rooted cultural norms significantly influence transformation efforts. Despite a growing body of global change management literature, limited empirical research addresses the interplay between cultural dynamics and change management within the Saudi context.ObjectiveThis study examines how change management techniques and cultural elements jointly affect employee engagement and performance in Saudi Arabia’s industrial sector. Kurt Lewin’s change management model serves as the theoretical foundation, providing a structured lens for analyzing transformation processes.MethodsA quantitative research design was adopted, using a self-administered survey completed by 477 employees from diverse industrial firms across Saudi Arabia. A pilot study ensured the instrument’s validity and reliability. Structural Equation Modeling (SEM) was employed to evaluate relationships among change management practices, cultural factors, and employee outcomes.ResultsThe findings reveal that leadership—when aligned with culturally appropriate practices—significantly enhances employee engagement and performance. Transparent communication, employee participation, and targeted training were identified as critical enablers of effective change. Furthermore, cultural factors moderated the impact of change management strategies, emphasizing the necessity of context-sensitive approaches.ConclusionThis study contributes theoretically by integrating cultural considerations into change management frameworks, addressing a gap in region-specific organizational research. Practically, the results offer actionable insights for leaders and HR professionals aiming to design culturally responsive change strategies. The novelty of this research lies in its empirical focus on the Saudi industrial sector, providing evidence-based guidance for managing change in culturally complex environments.